Screening of Selected Chemotherapeutant by using Primary Liver cell Culture of Labeo rohita (Hamilton, 1822) - Choudhary, Pushpa; Tripathy, Gayatri; Pani Prasad, K. (Fishery Technology, 2019)
Development of primary cell culture from livertissues of Labeo rohita was successfully completed byfollowing explant culture method. The L-15 mediasupplemented with 20% foetal bovine serum (FBS)at 28oC has resulted in good attachment andproliferation of primary culture. FBS is required forefficient attachment of liver explant but increasedsupplementation of FBS in media did not stimulatethe proliferation of cells. Radiation from liverexplant was first seen after 48 h of attached explant.The monolayer formation of liver cell culture wasobserved after twenty one days and it was subsequentlysub cultured for more than 10 times. The invitro cytotoxicity of a commonly used drugs (Oxytetracycline),chemotherapeutant (Benzalkonium chloride)and insecticide (Fipronil) was studied onprimary liver cell culture of L. rohita by assessing cellviability using tetrazolium (MTT) assay whichrevealed that Fipronil is most toxic compared to OTCand BKC. Reduction in cell viability was observedwith the increase in concentration ofchemotherapeutants. The IC50 values of OTC, BKCand Fipronil calculated from dose-response curvewere 76.43 Î¼g ml-1, 3.22 Î¼g ml-1 and 0.014 Î¼g ml-1respectively. The study revealed that primary cellculture from liver tissue of L. rohita can be used asa potentially bio-indicator for the in vitro screeningof the acute toxicities of Fipronil.